Poesia negro-feminina: discurso poético e empoderamento em Elisa Lucinda - Justino, Maria Edilene (2021)
To ponder over gender questions implies to understand how broad, challenging and complex these discussions are, since they involve cultural and socio-historical relations. Thus, in our study we stress the strength and power of the poetry produced by black women in Brazil, by looking at Elisa Lucinda’ s poetry and its unfolding in respect to gender, stereotype and empowering elements, supported by feminist and black feminisms, categories identified in her verses. We bring to light our results, after appreciating critically the selected corpus, taken from the following books: Eu te amo e suas estréias (2007); A fúria da beleza (2013); O Semelhante (2015); and Vozes Guardadas (2016), by Elisa Lucinda, observing her treatment of topics such as woman/women starting with Beauvoir (1970b), gender as seen by Lauretis and others (1994; 2019) and black feminism as debated by Davis (2016; 2017; 2018), Gonzalez (2019), Carneiro (2019), Hooks (2019), Kilomba (2019) and Ribeiro (2017; 2018; 2019. We also discuss stereotype, supported by Schmidt (2019), Collins (2019) and Gonzalez (2019). We approach the topic of body and eroticism, having Susan Bordo (1998), Borges (2013), Almeida (2012) and Lorde (2019) as theoretical supporters. To debate empowerment, we take Rute Baquero (2012), Joice Berth (2019) and Collins (2019) as our theoretical basis. While contextualizing poetry by black women in order to approach Lucinda’s poetry, we take into account differences in terms of insertion in the literary universe, if we compare female and male authors, blacks and whites as well. The denial of the writing by black women still can be identified in anthologies from the second half of the 20th century. We bring to light black women’s poetical voices, such as Auta de Sousa, a pioneer of Brazilian black poetry by women; Cadernos Negros, a historical mark for black literature in Brazil, which brings visibility to black poetry and black women’s poetry in particular. Finally, we come to the focus of our analysis, that is, Elisa Lucinda’s poetical irreverence, presenting a lyric “I” who wants to rewrite historical truth, give more visibility to black women’s voices and change their destinies. Through such deconstructions of stereotypes related to black women, we stress the female body in its poetic performance, which has been presented most times as the subjugated body by the media. We take this as a body able to destabilize patriarchal mentality becoming a body that consciously desires, taking sexuality as transgressive freedom. Female empowerment, thus, in poetical and erotic terms comes through in body and language, decolonizing the mind, words and discourses as well, becoming independent of the external, critical gaze of others. Finally, with our study we intend to contribute to the academic debate on gender, stereotype and empowerment, as posed in Lucinda’s poetry, giving priority to black women and their voices.